HUBUNGAN PENGUASAAN UNSUR-UNSUR INTRINSIK DAN EKSTRINSIK KARYA SASTRA FIKSI DENGAN KEMAMPUAN MENULIS CERPEN PADA SISWA KELAS VIII SMP NEGERI 3 SUNGAI KAKAP - Uci Laras Tiwi; Adisti Primi Wulan; Sri Kusnita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the relationship between students’ mastery of intrinsic and extrinsic elements of fictional literary works and their short story writing ability among eighth-grade students at SMP Negeri 3 Sungai Kakap. The research employed a quantitative method with a correlational approach. The population of this study consisted of all eighth-grade students, totaling 30 students. Data were collected using a multiple-choice objective test consisting of 25 items to measure students’ mastery of intrinsic and extrinsic elements of fictional literary works, and one essay test item to assess students’ ability to write short stories. The results of data analysis indicate that: (1) the total score for mastery of intrinsic and extrinsic elements of fictional literary works reached 23.76, with an average score per student of 79.20 from 30 respondents. This result shows that students’ mastery of intrinsic and extrinsic elements of fictional literary works falls into the good category; (2) the total score of students’ short story writing ability from the essay test reached 21.56, with an average score per student of 71.86, which is also classified as good; and (3) correlation analysis using the mean formula and Pearson product-moment correlation reveals that there is a relationship between mastery of intrinsic and extrinsic elements of fictional literary works and students’ short story writing ability. The research data show that the calculated r-value is greater than the r-table value (0.4052 > 0.361), indicating that the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected. Therefore, it can be concluded that there is a significant relationship between students’ mastery of intrinsic and extrinsic elements of fictional literary works and their short story writing ability at SMP Negeri 3 Sungai Kakap.